Share
Explore BrainMass

Spring Oscillations

A particle of mass ,m, is at rest at the end of a spring(force constant=k)hanging from a fixed support. At t=0 a constant downward forcd F is applied to the mass and acts for a time T. Show that after the force is removed, the displacement of the mass from its equilibrium position (x=Xe, where x is down) is:

x - Xe =F/k[cosW(t-T) - cosw(t)]

where w = omega

Solution Summary

This solution shows that after the force is removed, the displacement of mass from equilibrium position is x - Xe =F/k[cosW(t-T) - cosw(t)]. Steps are shown for the full derivations for where the concepts of Hooke's Law and period are used.

$2.19